Structural and Electrochemical Properties of Binary ZnO:Al Nanocomposites as Anode for Lithium-ion Batteries - Maisurah Mukhtar; Najiha Hamid; Syahida Suhaimi; Azwani Sofia Ahmad Khiar; Nur Athirah Mohd Taib; Peshawa Omer Amin (Faculty of Science and Technology, USIM, 2025)
Malaysian Journal of Science Health & Technology, Volume 10 Issue 2 Page (125–131)